2013
DOI: 10.1134/s0018143913040085
|View full text |Cite
|
Sign up to set email alerts
|

Influence of radiolysis on the yield of nanocellulose from plant biomass

Abstract: Radiolysis of plant biomass with doses of 200-300 kGy prior to dispersing by chemimechanical methods increases the yield of nanocellulose from cellulosic feedstock by more than a factor of two. Another advantage of radiation pretreatment of initial samples is the effect of radiation sterilization of isolated nano cellulose hydrogels, whereas the hydrogel obtained without preliminary irradiation rapidly suffers from the attack of molds during storage in the laboratory. Photolysis of plant raw material at a wave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…However, the production yield is very low (∼1.0%) indicating that the radiation treatment alone is insufficient for this purpose. 152 Therefore, researchers have coupled this technique with other mechanical or chemical techniques. For instance, Kuzina et al 152 increased the yield of nanocellulose production in an acid hydrolysis treatment from 34% to 75% with taking advantage of radiation techniques (at a dose of ∼200 kGy).…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the production yield is very low (∼1.0%) indicating that the radiation treatment alone is insufficient for this purpose. 152 Therefore, researchers have coupled this technique with other mechanical or chemical techniques. For instance, Kuzina et al 152 increased the yield of nanocellulose production in an acid hydrolysis treatment from 34% to 75% with taking advantage of radiation techniques (at a dose of ∼200 kGy).…”
Section: ■ Introductionmentioning
confidence: 99%
“…152 Therefore, researchers have coupled this technique with other mechanical or chemical techniques. For instance, Kuzina et al 152 increased the yield of nanocellulose production in an acid hydrolysis treatment from 34% to 75% with taking advantage of radiation techniques (at a dose of ∼200 kGy). Their finding also indicated that γ radiation penetrates into the bulk material, while the interaction of UV light with cellulose is more selective.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation